2019
DOI: 10.1016/j.heliyon.2019.e01603
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3-((2-chloroquinolin-3-yl)methylene)indolin-2-one derivatives produce anticancer efficacy in ovarian cancer in vitro

Abstract: A novel series of 3-((2-chloroquinolin-3-yl)methylene)indolin-2-ones were synthesized, using the ‘molecular hybridization approach’ and evaluated for anticancer efficacy. Eleven 3-((2-chloroquinolin-3-yl)methylene)indolin-2-ones ( LM01 to LM11 ) were synthesized and evaluated for in vitro cytotoxic efficacy in cancer (ovarian, prostate and colon) and two non-cancerous cell lines. Among the 3-((2-chloroquinolin-3-yl)methylene)indolin-2-one der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The flipped anionic PS binds to the Ca 2+ -dependent phospholipid-binding protein, annexin V [ 49 ]. We discovered and reported several potent apoptosis-inducing compounds [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In this study, the result of our morphological studies in MDA-MB-231 cells after incubation with our lead compounds, 4g and 4i, indicated that apoptosis was occurring ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…The flipped anionic PS binds to the Ca 2+ -dependent phospholipid-binding protein, annexin V [ 49 ]. We discovered and reported several potent apoptosis-inducing compounds [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In this study, the result of our morphological studies in MDA-MB-231 cells after incubation with our lead compounds, 4g and 4i, indicated that apoptosis was occurring ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolites with high ranking seem to be interacting with multiple microbiome species, for example Indolin-2-one is a tryptophan metabolite, likely of gut microbiome origin [ 77 ]. Indolin-2-one compounds have been identified as an effective cancer treatment, with indolin-2-one derivatives showing anticancer effects in vitro against ovarian cancer cells [ 78 , 79 , 80 ]. Louis et al [ 81 ] have also identified higher log blood harmane concentration in colon cancer and other cancers in comparison to those without cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 16 was obtained by the reaction of acid hydrazide 3 with 1-(4-aminophenyl)ethan-1-one in propan-2-ol at reflux for 15 h (Supplementary materials, Figures S23 and S24). The 3-methyleneindolin-2-one moiety is a part of naturally occurring compounds and is widely used for the design of biologically active compounds [35,36]. Thus, to incorporate this structural unit into the designed structure, hydrazide 3 was treated with indoline-2,3-dione in refluxing propan-2-ol for 2 h. The product 17 was isolated with a 73% yield (Supplementary materials, Figures S25 and S26).…”
Section: Chemistrymentioning
confidence: 99%